2020
DOI: 10.9734/jerr/2020/v12i417089
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood Spatial Pattern and Noise Disturbance in Benin City, Nigeria

Abstract: Noise has an environmental challenge is increasing due to urbanization, industrialization and modernization. While residential noise pollution could have adverse effect on health and social wellbeing, little attention has been directed towards investigating the implications of spatial pattern of neighbourhood facilities on noise pollution in Nigeria. This study assessed how noise disturbance is related to spatial pattern within two neighbourhoods in Benin City, Nigeria. Structured questionnaires were used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…Ali et al (2017) noted that acoustic discomfort causes fatigue, headaches, annoyance, changes in behavior and attitude leading to a decrease in intellectual working ability and sleep disorders. In a similar study done in Benin City, Nigeria, Oviasogie and Ikhudayisi (2019) revealed that the prominent sources of noise pollution in two residential neighborhoods were portable electricity generators and commercial activities. They also noted that other sources of noise pollution were the loudspeakers used by churches and mosques, highly amplified music from record shops, bells used by peddlers, hawkers, and salesmen of items to who advertise their wares and grinding machines.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Ali et al (2017) noted that acoustic discomfort causes fatigue, headaches, annoyance, changes in behavior and attitude leading to a decrease in intellectual working ability and sleep disorders. In a similar study done in Benin City, Nigeria, Oviasogie and Ikhudayisi (2019) revealed that the prominent sources of noise pollution in two residential neighborhoods were portable electricity generators and commercial activities. They also noted that other sources of noise pollution were the loudspeakers used by churches and mosques, highly amplified music from record shops, bells used by peddlers, hawkers, and salesmen of items to who advertise their wares and grinding machines.…”
Section: Literature Reviewmentioning
confidence: 96%